Pandangan Islam Dalam Memaknai Hakikat Manusia - Aryandika Firmansyah; M. Yazid Fathoni; Wismanto Wismanto; Dio Herfanda Bangun; Muhammad Hanif Nasution (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The mysteries of humanity are like the mysteries of nature: the more dimensions we know, the more we realize that there are still many unknown things. Humans are a symbol of the natural wonders created by God. There are people who have very attractive personalities and it is from their strong and noble personalities that they achieve success in society, become honorable people and are respected by society. Quraish Syihab in his book